Pandangan Imam Madzhab dalam Masalah Nafkah dan Relasi Hukum keluarga terhadap Fenomena Fatherless di Kecamatan Kraksaan - Afifa Syiddatul Auliya’; Fathullah Rusly; Nina Agus Hariati (Kartika: Jurnal Studi Keislaman, 2026)
The phenomenon of fatherlessness is the absence of a father's role in a child's life, whether physically, psychologically, or economically. This phenomenon is increasingly evident in various regions, including Probolinggo Regency, and has a direct impact on the fulfillment of children's rights, particularly the right to maintenance. This study aims to analyze the phenomenon of fatherlessness in Probolinggo through the perspective of islamic jurisprudence schools of thought regarding the obligation to provide maintenance and the relationship between them in islamic family law. The research method used is qualitative research with a normative-juridical and sociological approach, through a review of classical and contemporary islamic jurisprudence literature and an analysis of the social context of the community. The results show that all schools of thought agree on the father's obligation to provide maintenance to children, although there are differences in technical aspects and the conditions under which this obligation falls. These differing views have implications for family law relations, particularly in efforts to protect children's rights in cases of fatherlessness. This research is expected to contribute academically to the development of Islamic family law studies and serve as a reference in responding to the phenomenon of fatherlessness in society